First person - Madelyn Jackstadt (The Company of Biologists, 2022)
First Person is a series of interviews with the first authors of a selection of papers published in Disease Models & Mechanisms, helping early-career researchers promote themselves alongside their papers. Madelyn Jackstadt is first author on ' A multidimensional metabolomics workflow to image distribution and evaluate pharmacodynamics in adult zebrafish', published in DMM. Madelyn is a PhD student in the lab of Gary Patti at Washington University, St. Louis, MO, USA, and is interested in utilizing metabolomics, particularly isotope tracing, in zebrafish to investigate biological questions including drug effects and disease states.